Two decades of renewable energy ‘Talk’ in Australia - Muhammad Adnan Qureshi; M. Shahabuddin; Sidra Ishfaq (Sustainable Futures)
This research explores the discussions on renewable energy in Australia’s Federal Parliament over the past two decades (2001–2022), focusing on the political, economic, and ideological factors influencing policy decisions. Unlike previous studies that primarily assess policy outcomes, this study deeply explores the role of political rhetoric, climate scepticism, economic priorities, and international commitments in shaping renewable energy development. By analysing 390 parliamentary transcripts through content analysis, the study identifies key themes and narratives that have driven or hindered legislative actions and investment in the sector.The findings indicate that despite Australia’s formal commitments to global agreements like the Kyoto Protocol and the Paris Agreement, renewable energy policies have often been shaped by political interests rather than a long-term strategic vision. The research highlights the importance of stable institutions, unbiased regulatory frameworks, and broader stakeholder engagement to ensure consistent policy direction. By shedding light on the intersection of political discourse and energy governance, this study offers valuable insights into the challenges of renewable energy policymaking and suggests pathways toward a more sustainable and stable energy future for Australia.